COVID‐19–infected woman along with tuberculosis and psychogenic non‐epileptic seizures: A case report. Issue 10 (24th October 2021) - Nadershahbaz, Mahshid; Bidaki, Reza; Azimi, Saeed; Saghafi, Fatemeh
Abstract: During the COVID‐19 pandemic, we should not forget about chronic, underlying and important diseases, especially diseases that cause immune system deficiency, of which TB is one and may be missed. Also, we should pay attention to the past medical history of the patients and their drug‐drug interactions during the treatment period of COVID‐19. Our main clinical message is that diseases such as TB, which weaken the immune system, may predispose a person to COVID‐19 infection and COVID‐19 may exacerbate TB and it's mortality. On the other hand, diseases that target the lung tissue such as TB and COVID‐19, may have synergistic effects and increase mortality (for a patient whose lung capacity is reduced due to TB, superimposed COVID‐19 can worsen the situation). In addition, it may be necessary to take more serious considerations for COVID‐19 in low socio‐economy countries, such as Afghanistan, where TB is more prevalent Abstract : During the COVID‐19 pandemic, we should not forget about chronic, underlying, and important diseases, especially diseases that cause immune system deficiency, of which TB is one and may be missed. Also, we should pay attention to the past medical history of the patients and their drug‐drug interactions during the treatment period of COVID‐19. Our main clinical message is that diseases such as TB, which weaken the immune system, may predispose a person to COVID‐19 infection and COVID‐19 may exacerbate TB and its mortality. On the contrary, diseases that target the lung tissue such as TB and COVID‐19 may have synergistic effects and increase mortality (for a patient whose lung capacity is reduced due to TB, superimposed COVID‐19 can worsen the situation). In addition, it may be necessary to take more serious considerations for COVID‐19 in low socio‐economy countries, such as Afghanistan, where TB is more prevalent.